A comparison of the productivity of borrowings in written and spoken Sri Lankan English: A corpus-based study - Illangakoon, S.R. (University of Colombo, 2025)
Sri Lankan English (SLE) is a variety derived from British English (BE) and influenced by local languages and contextual necessities. Similar to other World Englishes, SLE has shown variation from BE in vocabulary, pronunciation, and grammar. This study aims to investigate vocabulary through the productivity of borrowings; i.e., words copied from local languages and linguistically integrated into SLE. Borrowings are one of the features that showcase the unique adaptation and development of the language highlighting its Asian and local identity. This will be investigated through the occurrence of types of borrowings in the data. The data were taken from the Sri Lankan component of the International Corpus of English (ICE-SL), a collection of written and spoken texts, developed for research into World Englishes. The borrowings were divided into established borrowings (community accepted), mid-range borrowings (emerging), and nonce borrowings (emerging). Dispersion of borrowings is a new measure posited by this researcher to identify established borrowings. In the written and spoken genres, the established borrowings formed the smallest category (14% and 22% respectively), while nonce borrowings formed the largest (56% and 52% respectively). Nonce borrowings also showed the emergence of new grammatical features with borrowings. The possessive ‘s’ used with borrowings in the written genre has been established and the current study posits the use of the possessive ‘s’ in the spoken genre. Although the productivity of borrowings, as measured by type counts, is low (1.44% in writing and 0.01% in speech), the cultural and contextual needs, as well as the use of grammatical features with borrowings, indicate the acceptance of borrowings by SLE users. The study also notedover 1000 instances of codeswitching in speech, highlighting a significant difference between the genres of speech and writing.
Keywords: Corpus study; Productivity; Sri Lankan English; Spoken genre; Written genre